2019
DOI: 10.4038/cjs.v48i1.7585
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and phytochemical properties of fresh juice produced from selected mango varieties

Abstract: Mango (Mangifera indica L.) is a seasonal and highly perishable yet nutritious fruit with different varieties. Further, processing of the fruit will extend the shelf life and increase the potentials of exploiting the underutilized varieties. This paper investigated the suitability of four Nigerian mango varieties (Lippen, Kent, Palmer and Saigon) for fresh juice production and also evaluated the quality attributes of the stored juice samples. Well ripen, firm mango fruits were processed into juice, packed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…38 reported that acidity of freshly prepared carrot juice is 0.38±0.17%. The increase in TA of carrot juice during the period of storage could be attributed to organic acid undergoing partial hydrolysis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…38 reported that acidity of freshly prepared carrot juice is 0.38±0.17%. The increase in TA of carrot juice during the period of storage could be attributed to organic acid undergoing partial hydrolysis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The saponin content was observed to decrease with increase in the storage period at both storage temperatures. Saponins have been revealed to possess cholesterol lowering properties, which makes it beneficial to humans (Babarinde et al, 2019).…”
Section: Phytochemical Properties Of African Star Apple Juice During ...mentioning
confidence: 99%
“…Mado, Kent, Tommy Atkin, Apple, and Julie are physicochemical and sensory cultivars common in the tropics (Wibowo et al, 2015). Mango is processed into secondary products to extend its shelf life (Babarinde et al, 2019). Pasteurization is a common heat treatment for acidic foods to extend shelf life and microbiological safety (Rawson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%